Utilization of Rice-Hush Charcoal to Improve Growth of Jabon Seedlings (Anthocephalus cadamba (Roxb.) Miq) on Subsoil Media. - Supriyanto Supriyanto; Fidryaningsih Fiona (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2010)
Bio-charcoal has been used widely in agriculture and forestry, especially in seedling production. It is not only as a source of fuel energy but the charcoal can also be used as a soil amandment for improving soil properties as an effort to improve crop growth and land rehabilitation. The purpose of this study was to determine the effect of adding rice-husk charcoal amendment to Jabon seedlins grown in the subsoil media. Treatment was provided in the form of five doses of rice-husk charcoa lthose were 0% (control), 2.5%, 5%, 7.5% and 10% (v / v) with 10 replicates, each treatment consisted of 3 units. The number of media (subsoil)treatment was 2 / 3 the volume polybag size 10 x 15 cm. Observations showed that the amandment of rice-husk charcoal to the subsoil improved significantly on height and the total dry weight (biomass) of Jabon seedlings compared to controls. The amandment of rice-husk charcoal 5% (v / v) in the subsoil produced the best growth of Jabon seedlings or increasd from 27.42% to 65.64% for total dry weight (biomass) compared to control.